2017
DOI: 10.15171/mejdd.2017.78
|View full text |Cite
|
Sign up to set email alerts
|

The Association between Modulating Inflammatory Cytokines and Constipation of Geriatrics in Iran

Abstract: BACKGROUND The effect of changes in intestinal microbiota on constipation is contraversial. Constipation is more prevalent in elderly. Therefore, the current study was designed to assess the role of modulating inflammatory cytokines in old age patients with constipation by evaluating the serum levels of tumor necrosis factor alpha (TNF-α), interleukin 1 (IL-l), and interleukin 6 (IL-6). METHODS This case-control study was done on 100 participants, aged 65 years or higher, with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 35 publications
2
35
0
Order By: Relevance
“…In this study, the association between constipation and Oscillospira was also observed. Considering the low levels of inflammation exists both in constipated mice and human (Mokhtare et al, 2017 ; Ren et al, 2017 ), and the reduced abundance of Oscillospira in human gut with inflammation (Walters et al, 2014 ), it is speculated that the change of Oscillospira may be closely related to the development of constipation.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the association between constipation and Oscillospira was also observed. Considering the low levels of inflammation exists both in constipated mice and human (Mokhtare et al, 2017 ; Ren et al, 2017 ), and the reduced abundance of Oscillospira in human gut with inflammation (Walters et al, 2014 ), it is speculated that the change of Oscillospira may be closely related to the development of constipation.…”
Section: Discussionmentioning
confidence: 99%
“…Khalif et al observed that constipation was correlated with significant alterations in the fecal flora, gut permeability (leaky gut), and immune response, and that alleviation of constipation tended to reverse these changes [ 17 ]. Intestinal conditions such as constipation could affect immunity by altering gut microflora and permeability, leading to hyper-secretion of proinflammatory or inflammatory biomarkers, such as chemokines and cytokines [ 39 , 42 ]. Cirali et al found that neopterin, IL-6, and IL-12 and levels of constipated children were higher than in the non-constipation group [ 43 ], indicating that subclinical inflammation existed in patients with constipation.…”
Section: Discussionmentioning
confidence: 99%
“…Cirali et al found that neopterin, IL-6, and IL-12 and levels of constipated children were higher than in the non-constipation group [43], indicating that subclinical inflammation existed in patients with constipation. Mokhtare et al also showed higher levels of TNF-α, IL-1, and IL-6in geriatric patients with chronic constipation, compared with healthy controls [42]. In experiments, TNF-α was required to produce antigen-specific IgE and to induce T-helper 2 cytokines and chemokines in allergic rhinitis [44,45].…”
Section: Plos Onementioning
confidence: 93%
See 1 more Smart Citation
“…IL-8,also known as CXCL8, is a chemokine with multiple functions in a variety of physiological and pathological processes [27,28]. Recently it was found that the serum levels of cytokine TNF-α, IL-1 IL-6, and IL-12 were reportedly increased in geriatric and paediatric patients with chronic constipation [9,29]. It was speculated that the intestinal dysbiosis in patients with chronic constipation may lead to the elevation of serum pro-in ammatory cytokines [29].…”
Section: Introductionmentioning
confidence: 99%